Improving Speaking Skills Through the Sociodrama Method in Grade V Students at Elementary School - Rospia Fidmas; Ribka L. Ririhena; Sarah Sahetapy (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The low speaking skills of fifth-grade students at Elementary School 2 Ambon in learning Indonesian are the background of this research. Initial conditions indicate that students' abilities are still below the Minimum Completion Criteria. This research aims to improve students' speaking skills through the application of the sociodrama method. The type of research used is Classroom Action Research (CAR) model Kemmis and McTaggart. The research was conducted in two cycles involving 25 students as research subjects. Each cycle consists of planning, implementation, observation, and reflection stages. Data collection techniques were carried out through observation, oral tests, and documentation. The results of the study showed a consistent increase in speaking skills. The average class score increased from 62.60 (sufficient) in the pre-cycle to 69.20 in the first cycle and reached 79.76 (good) in the second cycle. The percentage of classical completeness increased drastically from 0% in the pre-cycle to 56% in the first cycle and reached 100% in the second cycle. The improvement includes aspects of intonation, pronunciation, fluency, expression, and self-confidence. This study proves that the sociodrama method is effective in creating an active, enjoyable, and student-centered learning environment, and provides practical references for teachers in their efforts to improve speaking competence in elementary schools.